Sistem Pendukung Keputusan Pemilihan Supplier Terbaik Menggunakan Multi Factor Evaluation Process (MFEP): Penelitian - Yungki Gunawan; Arif Budimansyah P.; Wawan Kusdiawan; Rolles Herwin; Jajang Mulyana; Ahmad Mubarok; Cepi Indra Grahana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Supplier selection is the most important thing for a company to find out the best supplier who will supply products to the company, especially at Toserba Fajar Karawang. The supplier selection process at Toserba Fajar Karawang is still not systematic enough so that the supplier selection process is not accurate. Therefore, a decision support system is needed in supplier selection which is part of the computer information system used by a company which will later process data into information to make a decision. The purpose of this study is expected to help in the goods order section in the process or determine the selection of the best supplier selection built using the Multifactor Evaluation Process (MFEP) method, this method was chosen because it can provide subjective and intuitive considerations in a decision so that these considerations are in the form of giving weight to multifactors that are considered important to the alternatives that have been selected. Based on the final result, namely a decision support system for selecting the best supplier where users can input and get the stored data, namely criteria data, sub-criteria data, supplier data, product data, selection data, and report data.